An analysis of the forward stroke as used in a wild water kayak on flat waters - Janura, M.; Kratochvil, J.; Lehnert, M.; Vaverka, F. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2005)
The forward stroke is one of the basic motion activities that are typically used for canoeing in white water. Kinematic analysis (4 women, 5 men; junior representatives and talented competitors) of records from three cameras was used. The movement of the kayak was carried out with maximal velocity. General parameters of the stroke on the left and right side of the kayak were determined utilizing the APAS system. Lower velocity losses in the catch and pull phase of the paddle, a shorter time of the pull phase, higher frequency of the strokes are typical for kayakers with better levels of efficiency.The movement of the right and left wrist of these competitors in the frontal plane is more symmetrical.The deviation of the trunk is less in the sagittal plane as well as the sideways movement of the kayak.